PERAN GURU IPS DALAM MEMBENTUK KARAKTER DISIPLIN SISWA DI SMP TUNAS PERSADA MALANGBONG GARUT - Rika Kartika; Lili Dianah; Sudarmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the role of social studiesteachers in shaping students’ disciplinary character atSMP Tunas Persada Malangbong Garut, the obstaclesfaced, and the efforts made to overcome theseobstacles. This study used a qualitative researchmethod with a literature study approach. Data were obtained from various relevant sources such as books, scientific journals, research articles, and otherdocuments related to the research topic. Data collection techniques were carried out through contentanalysis of various sources related to the role of socialstudies teachers and the formation of students’ disciplinary character. The results of the study indicatethat social studies teachers have an important role in shaping students’ disciplinary character throughmotivation, disciplinary habituation, role modeling, andthe enforcement of rules in the learning process. Social studies teachers also play a role in instillingresponsibility, obedience to rules, and mutual respectamong students. However, there are several obstaclesin its implementation, such as students’ low awarenessof the importance of discipline, peer environmentalinfluences, lack of family attention, and excessivegadget use. To overcome these obstacles, socialstudies teachers make various efforts, such as providing advice and motivation, implementingdisciplinary habituation, giving good examples, andcollaborating with students’ parents. Therefore, theformation of students’ disciplinary character requirescooperation between teachers, families, and theschool environment in order to run optimally.